Effective Coverage Targets for Ocean Protection. Issue 6 (21st April 2016) - O'Leary, Bethan C.; Winther‐Janson, Marit; Bainbridge, John M.; Aitken, Jemma; Hawkins, Julie P.; Roberts, Callum M.
Abstract: The UN's globally adopted Convention on Biological Diversity coverage target for marine protected areas (MPAs) is ≥10% by 2020. In 2014, the World Parks Congress recommended increasing this to ≥30%. We reviewed 144 studies to assess whether the UN target is adequate to achieve, maximize, or optimize six environmental and/or socioeconomic objectives. Results consistently indicate that protecting several tens‐of‐percent of the sea is required to meet goals (average 37%, median 35%, modal group 21–30%), greatly exceeding the 2.18% currently protected and the 10% target. The objectives we examined were met in 3% of studies with ≤10% MPA coverage, 44% with ≤30% coverage, and 81% with more than half the sea protected. The UN's 10% target appears insufficient to protect biodiversity, preserve ecosystem services, and achieve socioeconomic priorities. As MPA coverages generated from theoretical studies inherently depend on scenario(s) considered, our findings do not represent explicit recommendations but rather provide perspective on policy goals.